2009
DOI: 10.1002/pola.23701
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of H‐atom transfer in imidazoline‐, imidazolidine‐, and pyrrolidine‐based alkoxyamines: Consequences for nitroxide‐mediated polymerization

Abstract: The H‐atom transfer reaction was studied for a series of imidazoline, imidazolidine, and pyrrolidine‐based alkoxyamines containing either isobutyrate‐2‐yl or 1‐phenylethyl alkyl fragments. The CO bond homolysis rate constants and activation energies were determined by 1H NMR product analysis as a function of temperature. Inter‐ and intramolecular H‐atom transfer reactions were distinguished by examination of alkoxyamine thermolysis products in the absence and in the presence of a radical scavenger (thiophenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…However, no ambiguous discussions were provided on the origin of this effect. At a first glance, although this led to apparently contradictory measurements [10,15,16], such small differences in k d may look unimportant, but nevertheless, we have recently shown that the fate of NMP [11,12,17] and the occurrence of side-reactions [18] depends on such small differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, no ambiguous discussions were provided on the origin of this effect. At a first glance, although this led to apparently contradictory measurements [10,15,16], such small differences in k d may look unimportant, but nevertheless, we have recently shown that the fate of NMP [11,12,17] and the occurrence of side-reactions [18] depends on such small differences.…”
Section: Introductionmentioning
confidence: 99%
“…0.5%, sensitivity of CIDNP is a valuable tool for screening the occurrence of H-transfer reaction in alkoxyamine. Contrary to 2a, alkoxyamine 3a exhibits high fraction of H-atom transfer (at 95 °C, 30% and 15% for intramolecular proton transfer and intermolecular H-transfer reactions, respectively) [10]. Thus, as mentioned above, one would expect positive polarization on a(-H).…”
Section: Kinetics Of Cidnpmentioning
confidence: 98%
“…In previous articles [9,10] we have reported the kinetics of thermolysis with long time delays between scans or at low temperatures where all NMR lines were nonpolarized. This article concerns the cases of high thermolysis temperature and short time delays when radical concentration is high enough to produce intensive Chemically Induced Dynamic Nuclear Polarization (CIDNP).…”
Section: Scheme 1 the Mechanism Of Nmp With Side Reactions Of H-atommentioning
confidence: 99%
See 2 more Smart Citations